Everything and nothing changes: Fast-food employers and the threat to minimum wage regulation in Ireland. (February 2014) - O'Sullivan, Michelle; Royle, Tony
Ireland's selective system of collective agreed minimum wages has come under significant pressure in recent years. A new fast-food employer body took a constitutional challenge against the system of Joint Labour Committees (JLCs) and this was strengthened by the discourse on the negative effects of minimum wages as Ireland's economic crisis worsened. Taking a historical institutional approach, the article examines the critical juncture for the JLC system and the factors which led to the subsequent government decision to retain but reform the system. The article argues that the improved enforcement of minimum wages was a key factor in the employers' push for abolition of the system but that the legacy of a collapsed social partnership system prevented the system's abolition.